AN ELECTRONIC AUDIO-VISUAL BASED STRATEGY FOR BETTER SOPHOMORES’ EFL PRONUNCIATION SKILLS - Mai Mohsen, Prof. Eman Mohamed Abd el-haq (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study aims at investigating the effectiveness of utilizing Electronic Audio-Visual based strategy on developing EFL pronunciation skills among sophomores at the Faculty of Specific Education, Zagazig University, Egypt. This study adopted a quasi-experimental design. The participants of the study were divided into two groups; control group (N=20) and experimental one (N=20). For collecting data, an oral EFL pronunciation test was pre- and post-administered to both groups. Obtained data were analyzed using SPSS. Findings revealed that there was a statistically significant difference between the mean scores of the experiment and the control groups for favor of the experimental one. There was a statistically significant difference between the mean scores of the experimental group in the pre and posttests for favor of the post one. Electronic Audio-Visual based strategy is effective in developing EFL pronunciation as it included purposeful material that increased students’ engagement and interaction and provided them with multiple opportunities of exposure to the target language the thing that helped in enhancing their EFL pronunciation,. Based upon the study results, both theoretical and practical aspects of EFL pronunciation should be taught parallel to each other in an integrated manner; the practical part goes along with the theoretical one not separately. EFL pronunciation should be practiced in real- life situations.